Addressing Dynamism in E-negotiations by Workflow Management Systems - Bassil, Sarita; Benyoucef, Morad; Keller, Rudolf K.; Kropf, Peter (My University, 2002)
Workflows (Wfs) are a major enabling technology for e-commerce. In our research, a Combined Negotiation (CN) is modeled and enacted using Wf technology. The model-ing task captures the sequencing of the individual negotia-tions as well as the dependencies between them, and the enacting task runs the model. A CN support system (CON-SENSUS) is used by the user to perform both tasks. Sup-porting dynamic modifications to the model during run-time should increase the benefits of our approach. In this paper, we highlight the need for such support by identify-ing the dynamic aspects that can occur while negotiating the different items of a package (i.e., the CN object). To address these aspects, we experimented using ADEPT, a Wf Management System supporting dynamism. This leads us to discuss the Wf Reference Model of the Wf Manage-ment Coalition, and suggest a “dynamic” extension to the current functional areas and architecture.